Computational identification of immune-related lncRNA signature for predicting the prognosis and immune landscape of human glioblastoma multiforme - Shi, Dongjie; Zhong, Wenjie; Liu, Dan; Sun, Xiaochuan; Hao, Shilei; Yang, Yaying; Ao, Lei; Zhou, Junjie; Xia, Yongzhi; Zhou, Yudong; Yu, Hua; Xia, Haijian (Frontiers in Immunology, 2022)
Emerging evidence showed the critical roles of immune-related long noncoding RNAs (ir-lncRNAs) in tumor progression and prognosis assessment. However, identification of ir-lncRNAs and their clinical significance in human glioblastoma multiforme (GBM) remain largely unexplored. Here, we designed a computational frame based on immune score to identify differentially expressed ir-lncRNAs (DEir-lncRNAs) from the The Cancer Genome Atlas (TCGA) GBM program. The immune-related lncRNA signature (IRLncSig) composed of prognosis-related DEir-lncRNAs selected by Cox regression analysis and its clinical predictive values were verified, which was further validated by another dataset from Gene Expression Omnibus database (GEO). Subsequently, we evaluated IRLncSig in immune cell infiltration, immune checkpoint inhibitor (ICI) biomarkers, O6-methylguanine-DNA methyltransferase (MGMT) gene expression, and biological function. After calculation, five prognosis-related ir-lncRNAs were included in the establishment of IRLncSig. The risk assessment based on IRLncSig indicated that the high-IRLncSig-score group was significantly associated with poor prognosis (p<0.001), significant aggregation of macrophages (P<0.05), higher ICI biomarker expression, and MGMT gene expression (p<0.05). Signature-related lncRNAs may be involved in immune activities in the tumorigenesis and progression of GBM. In summary, the novel IRLncSig shows a promising clinical value in predicting the prognosis and immune landscape of GBM.